Potential of Water Vending Machine to Remove Trihalomethanes and Heavy Metals During High and Low Water Seasons in Petropavlovsk - Dėdelė, A.; Nikiforov, N.I.; Madieva, A.N.; Miškinytė, A. (Pol. J. Environ. Stud., 2022)
The potential of water vending machine to remove chloroform (CHCl3), bromoform (CHBr3), bromodichloromethane (CHBrCl2), lead (Pb2+), and chromium (Cr6+) during high and low water seasons was investigated in Petropavlovsk, Kazakhstan. The water samples were collected from the water supply network during the high and low water seasons and were analyzed for CHCl3, CHBr3, CHBrCl2, Pb2+, and Cr6+. The retention coefficients of CHCl3 by the water vending machine were 54.3% and 67.4% during the high and low water seasons, respectively. Pb2+ concentrations decreased by 88.9% and 84.5% during the high and low water seasons, respectively. The concentrations of CHCl2Br were increased by 26.7% during the high water season, while during the low water season, this pollutant was removed completely. CHBr3 was completely removed during both seasons, while Cr6+ was removed during the low water season. Statistically significant differences were found in the concentrations of chloroform and lead between the classically and advanced purified water during the high and low water seasons (p<0.05). Meanwhile, statistically significant differences in the concentrations of bromoform between the classically and advanced purified water were only found during the low water season (p<0.05).
Keywords: drinking water; trihalomethanes; heavy metals; water vending machine